Determinants of childbirth in Russia: a micro-data approach - Kazuhiro, Kumo (Вестник ВГУ. Серия: Экономика и управление, 2010)
This paper uses the micro-data from the Russia Longitudinal Monitoring Survey (RLMS) to identify factors that explain fertility between 1995 and 2004. An overview of nationwide birth dynamics in post-Soviet Russia shows that not only changes in economic conditions move in lockstep with the overall birth rate trend, as has been pointed out by numerous researchers, but so too do proximate determinants of fertility, and suggests that rises and falls in the total fertility rate in Russia are also affected by factors such as demographic timing effects. Although few studies employing micro-data have been conducted, it is frequently argued that the shrinking of the economy during the transition to the market economy was the reason for the decline in the birth rate. Finally, the paper examines, from a demographic perspective, the measures to encourage couples to have children that were introduced in the last days of the Putin Administration, which ended in May 2008.